Taiwanese green propolis ethanol extract promotes adipocyte differentiation and alleviates TNF-α-mediated downregulation of adiponectin expression. (October 2020) - Chen, Yue-Wen; Chien, Yi-Hsuan; Yu, Yu-Hsiang
Graphical abstract: Highlights: TGP ethanol extract promotes the adipocyte differentiation and increases adiponectin expression. TGP ethanol extract alleviates norepinephrine-induced lipolysis in adipocytes. TGP ethanol extract reverses the inhibition of TNF-α on adipocyte differentiation and adiponectin expression in adipocytes. Abstract: The objective was to examine the effects of Taiwanese green propolis (TGP) ethanol extract on adipocyte differentiation and lipolysis. TGP ethanol extract significantly enhanced the differentiation of murine mesenchymal stem cells into adipocytes, and this was accompanied by an increase in intracellular triglyceride content and adiponectin levels. TGP ethanol extract significantly increased the expression of adipogenic transcription factor-associated genes in murine mesenchymal stem cells after hormonal induction of adipogenesis. TGP ethanol extract was able to alleviate norepinephrine-induced lipolysis in differentiated adipocytes, which was accompanied by a decrease in lipolytic gene expression. Besides, TGP ethanol extract could reduce the tumor necrosis factor-α (TNF-α)-mediated inhibition of adiponectin gene expression and secretion during adipogenic differentiation of mesenchymal stem cells and in differentiated adipocytes. These results demonstrate that TGP ethanol extract enhances adipocyte differentiation and is capable of reversing the inhibitory effects of TNF-α on adipocyte differentiation and adiponectin expression in differentiated adipocytes.